Inheriting Abraham : the legacy of the patriarch in Judaism, Christianity, and Islam - Levenson, Jon Douglas (Library of Jewish ideas., 2012)
"Jews, Christians, and Muslims supposedly share a common religious heritage in the patriarch Abraham, and the idea that he should serve only as a source of unity among the three traditions has become widespread in both scholarly and popular circles. Inheriting Abraham boldly challenges this view, demonstrating Abraham's distinctive role in each tradition, while delineating the points of connection as well. In this sweeping and provocative book, Jon Levenson subjects the powerful story in Genesis of Abraham's calling, his experience in Canaan and Egypt, and his near-sacrifice of his beloved son Isaac to a careful literary and theological analysis. But Levenson also explores how Judaism, Christianity, and Islam have given unique distinctive interpretations to these narratives, often reimagining Abraham and his life in mutually exclusive ways. Historically, the three traditions have differed sharply over what Abraham's life foreshadows, how the Abrahamic community is constituted and sustained, and what practices the patriarch's example authorizes. In these disputes, Levenson finds illuminating signs of profound and enduring theological divergences alongside the commonalities. A stunning achievement that is certain to provoke debate, Inheriting Abraham traces how each community has come to revere Abraham as an exemplar of its own distinctive spiritual teachings and practices. This probing and compelling book also reveals how the increasingly conventional notion of the three equally "Abrahamic" religions derives from a dangerous misunderstanding of key biblical and Qur'anic texts, fails to do full justice to any of the traditions, and is often biased against Judaism in subtle and pernicious ways."--Provided by publisher